Association of indoor temperature and air quality in classrooms based on field and intervention measurements. (1st February 2023) - Zhang, Xiaojing; Zhao, Caixia; Zhang, Tianyang; Xie, Jingchao; Liu, Jiaping; Zhang, Nan
Abstract: To investigate the variation of classroom environment during typical lecture hours, repeated field measurements and intervention experiments for indoor temperature were carried out in a typical class (95 min in duration, 0.32–0.39 person/m 2 of occupants density) in a spring semester of a university in Beijing. Environmental data were recorded every 5 min, including indoor temperature, relative humidity and carbon dioxide (CO2 ) concentration. Additionally, volatile organic compounds (VOCs) were sampled and indoor air quality (IAQ) were evaluated repeatedly. The results of field measurements showed the average air temperature in the classroom ranged from 21.2 ± 0.8 °C to 26.8 ± 0.7 °C, relative humidity ranged from 23.1 ± 1.8% to 57.5 ± 0.2%, and the average concentrations of CO2 and total volatile organic compounds (TVOC) were 1, 291–1, 833 ppmv and 159-1, 178 ppbm respectively. The subjective evaluations collected during intervention experiments showed that perceived odor intensity by visitors upon entering the room increased significantly, meanwhile the satisfaction and acceptability of air quality reduced considerably at the indoor temperature of 27 °C than that at 24 °C. Present results suggest when the indoor temperature rises, it is necessary to increase the outdoor air supply rate to ensure air freshness in classrooms. Subsequently, the calculated CO2 emission rate by students increased by 0.54 L/h per person for every 1 °C rise in indoor temperature. Corresponding to the control target of indoor CO2 concentration of 1, 000 ppmv, the outdoor air ventilation rate required to eliminate occupant-generated pollution needs to be increased by 0.25 L/s per person. Highlights: The air quality in a classroom during typical lecture periods was investigated. The CO2 emission rate of college students was estimated using indoor CO2 levels. Perceived air quality was reduced significantly as indoor temperature increased. Personal CO2 emission rate increases by 0.54 L/h for 1 °C rise in temperature. Higher outdoor air supply rate is recommended when indoor temperature rises.